Transposon-Directed Insertion-Site Sequencing Reveals Glycolysis Gene gpmA as Part of the H2O2 Defense Mechanisms in Escherichia coli - Myriam Roth; Emily C. A. Goodall; Karthik Pullela; Vincent Jaquet; Patrice François; Ian R. Henderson; Karl-Heinz Krause (MDPI AG, 2022)
Hydrogen peroxide (H2O2) is a common effector of defense mechanisms against pathogenic infections. However, bacterial factors involved in H2O2 tolerance remain unclear. Here we used transposon-directed insertion-site sequencing (TraDIS), a technique allowing the screening of the whole genome, to identify genes implicated in H2O2 tolerance in Escherichia coli. Our TraDIS analysis identified 10 mutants with fitness defect upon H2O2 exposure, among which previously H2O2-associated genes (oxyR, dps, dksA, rpoS, hfq and polA) and other genes with no known association with H2O2 tolerance in E. coli (corA, rbsR, nhaA and gpmA). This is the first description of the impact of gpmA, a gene involved in glycolysis, on the susceptibility of E. coli to H2O2. Indeed, confirmatory experiments showed that the deletion of gpmA led to a specific hypersensitivity to H2O2 comparable to the deletion of the major H2O2 scavenger gene katG. This hypersensitivity was not due to an alteration of catalase function and was independent of the carbon source or the presence of oxygen. Transcription of gpmA was upregulated under H2O2 exposure, highlighting its role under oxidative stress. In summary, our TraDIS approach identified gpmA as a member of the oxidative stress defense mechanism in E. coli.